Sahihayn'de kadın karşıtı görünen hadislerin sened ve metin açısından değerlendirilmesi (dirâsa tahliliye) - SURCHI, KHAIRALDEEN AHMED ABDULLAH (Fırat Üniveristesi, 2021)
Bu araştırma, görünürde kadınların eksikliğini ifade eden bir grup sahih hadisin Sahih-i Buhari ve Sahih-i Müslim'de yer alması hakkındadır. Bu rivayetlerin tahricini, hükmünü, sened ve metnine yönelen sorulara ve şüphelere cevap vererek çalışmamızda bu hadisleri sened ve metin açısından ele aldık. Bu metinlerinin doğru anlamlarını, sebeb-i vürüdlerini ve hadislerin münasebetlerini dikkate alarak açıklıyor ve âlimlerin bu rivayetler hakkındaki sözlerini ele alıp tartışıyoruz. İslam ve sahih hadislerin bu ithamlardan beri olduklarını ortaya koymaya çalışıyoruz. Bunlar, Sahîhayn'de geçen yedi hadistir: Birinci hadis: Ebû Saîd el-Hudrî'nin hadisidir ki, bu hadiste kadınlar hakkında üç mühim konu ele alınmıştır: Kadınların çoğunun Cehennem'lik olduğu, akıl ve dinî mevzularda eksik olmaları ve onların şahitlikteki konumu. İkinci hadis: "İşlerini bir kadına bırakan topluluk asla iflah olmaz." Üçüncü hadis: " Bilin ki, kadın şeytan sûretinde gelir ve şeytân sûretinde gider." Dördüncü hadis: " kadın bir eyeği kemiğinden yaratılmıştır. Eyeği kemiğinin en eğri yeri yukarı kısmıdır..." Beşinci hadis: "Eğer Havva olmasaydı, kadın cinsi eşine hıyanet etmezdi." Altıncı hadis: "Namazı, kadın, eşek ve köpek bozar." Yedinci hadis: "Kadında, atta ve evde uğursuzluk vardır." Bu araştırma bir önsöz, bir giriş, yedi bölüm ve bir sonuçtan oluşmaktadır. Önsözde araştırmanın önemi, amaçları, bu konuyu seçme nedenleri vb. konuları ele aldık. Giriş bölümünde İslam öncesi dönemde çeşitli milletler arasında kadının konumunu ve kadının İslam'la kazandığı onurlu durumunu ve sahip olduğu hakları kısaca ele aldık. Ayrıca Sahîhayn'in ümmet nezdinde kabulünü ve bu iki eserde yer alan hadislerin sıhhatin en yüksek mertebesini oluşturduğunu açıkladık. Bu hadislerin her birini, müstakil bölümlerde tek tek ele aldık. Sonuç bölümünde ise en önemli sonuç ve tavsiyelere yer verdik. Anahtar Kelimeler: Hadis, Sened, Metin, Kadın, Noksanlık.

This research deals with the study of a group of authentic hadiths contained in Sahih al-Bukhari and Sahih Muslim in the matter of women, as it is understood from their appearance that there is a diminution of women, and in our research we deal with these hadiths from the point of view of studying the chain of transmission and the text, where I am interested in extracting the hadiths and their rulings, and we answer suspicions And questions about the chain of narrators and the text, and we explain the correct meanings of their texts, taking into account the mind for their occurrence and their occasions, and we bring the sayings of the scholars about them and discuss them, and we exonerate Islam and the authentic hadiths from these accusations. These are seven hadiths mentioned in the two Sahihs: The first hadith: The hadith of Abu Saeed al-Khudri, where three important issues came in the matter of women: the majority of women will be in Hell, the issue of their lack of reason and religion, and the issue of their testimony. The second hadith: "A people who are in charge of a woman will not succeed." The third hadith: "A woman kisses in the form of a devil and contemplates in the form of a devil." Fourth hadith: "They were created from a rib, and the most crooked thing in the rib is the top…" The fifth hadith: "If it wasn't for Eve, no female would have betrayed her husband." The sixth hadith: "Prayer is interrupted by a woman, a donkey, and a dog." The seventh hadeeth: "But bad luck is in three: the woman, the horse, and the house." This research consists of an introduction, a preface, an introduction, seven sections, and a conclusion. In the preface, I dealt with the importance of the research, its objectives, reasons for choosing, and so on. In the introduction, I dealt with the condition of women in the pre-Islamic eras among different nations in a nutshell, and her honorable condition and her guaranteed rights in the shadow of true Islam, and she dealt with a statement of the acceptance of the two Sahihs and what was stated in them with the nation with the highest degree of validity. Each of these hadiths were dealt with separately one by one in a separate section of the seven investigations, and the conclusion dealt with the most important results and recommendations. Keywords: hadith, bond, text, woman, imperfection.
Keywords: Din